MORPHOLOGYCAL, ELEMENTAL CONTENT, AND PHYSICAL PROPERTIES OF CLEANED CLINOPTITOLITE ZEOLITE (10X) USING SONICATION AND MICROWAVE - Puspita, Endah; Naibaho, Marzuki; Ramlan, Ramlan; Ginting, Masno (Indonesian Physical Review, 2023)
This research was conducted to determine the morphology, elemental content and physical properties of the zeolite samples before and after cleaning. The characterization used in this study is the Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). Based on the results of SEM-EDX, it was shown that the 200 mesh zeolite sample and the zeolite that passed the filter had a non-spherical particle shape and no visible pores on the surface, while the microwave zeolite sample had an aggregate shape and visible pores on the particle surface which were very clear. In addition, in the 200 mesh zeolite sample, filtered zeolite and microwave zeolite each had an Al content percentage of 1.64%, 3.18 and 3.80% and a Si content of 7.58%, 15.15% and 18 .38%.